Tourism and climate in Lisbon: an assessment based on weather types - Machete, Raquel (2014)
Although climate is perceived as an essential part of tourism, influencing touristic regional and seasonal distribution patterns, ideal climate conditions for tourism are often assumed, rather than demonstrated. After reviewing the distinct tools that have been applied in order to evaluate climate potential for tourism, as well as tourists’ preferences, Besancenots’ weather-types method was chosen. This model was adapted and applied to Lisbon, evaluating the suitability of the summer season for tourism activities. The resulting weather type pattern was then crossed with the seasonal tourist demands (visitation statistics), allowing to conclude that even when the weather is categorized as extremely hot (type 7) or unfavourable for tourism (type 8) it does not reflect in the room occupation rates of the city of Lisbon, reinforcing recent advances in tourism climatology, that defy expert based thresholds of thermal preferences and comfort. A reformulation of the weather type model with our findings can be a useful tool for future assessments of tourist potential under projected climate changes.